Knitting Asia, Weaving Development Globalization of the Korean Apparel Industry - Lee, Joonkoo; Kwon, Hyunji; Lim, Hyun-Chin. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"This edited collection provides a rare look at the dynamic growth and multinationalization of Korean apparel firms. Despite their economic and social significance at home and abroad, little attention has been paid to the evolving nature of their business and strategies. This volume highlights their contributions as well as the challenges they are confronting in the fast-changing global apparel industry." - Kihak Sung, Chairman/CEO of Youngone Corporation and Former President of the International Textile Manufacturers Federation (ITMF) "The Korean apparel industry is an intriguing case in the study of industrial development because it was one of Korea's leading export sectors in the 1970s and 1980s, and then Korea adopted a critical middleman role in the subsequent internationalization of the apparel global value chain (GVC) since the 1990s. This edited volume highlights this new phase of globalization and regionalization by zooming in on Korean multinational first-tier suppliers and their role in fostering the expansion of the apparel GVC in Southeast Asia, Central America and other global regions." - Gary Gereffi, Emeritus Professor of Sociology and Director of the Global Value Chains Center at Duke This book offers a fresh look at the global apparel industry, focusing on Korean multinational corporations (MNCs) and their growing role in building regional connections and shaping economic and social development in Asia. Focusing on the multinationalization of Korean apparel firms over the past decades and their upgrading to first-tier suppliers in apparel global value chains, this edited volume highlights a host of new challenges these emerging MNCs confront in the rapidly changing global apparel industry and provides an in-depth view of their expanding role and adaptive strategies in configuring regional connections in post-Pandemic Asia. Joonkoo Lee is an Associate Professor in the School of Business at Hanyang University, Seoul, Republic of Korea. Hyunji Kwon is a Professor of Sociology at Seoul National University, Seoul, Republic of Korea. Hyun-Chin Lim is a Professor Emeritus of Sociology and Director of the Civil Society Program in Asia Center at Seoul National University, Seoul, Republic of Korea.
1. Introduction: Globalization, Value Chain Governance and Supplier Experimentation (Joonkoo Lee, Hyunji Kwon and Hyun-Chin Lim) -- 2. Expanding Overseas, Becoming Multinational, and Moving up the Chain: Three Waves of Globalization in the Korean Apparel Industry (Joonkoo Lee and Hyun-Chin Lim) -- 3. Korea's Multinational Garment Suppliers: Growth through Disintermediation (Solee Shin) -- 4. Toward a Bipolar Apparel GVC? From the Perspective of First-Tier Suppliers (Hyunji Kwon, Jinsun Bae, Joonkoo Lee and Sun Wook Chung) -- 5. A Hidden Champion? An Experimental Journey for Digital Integration of a First-Tier Supplier in the Apparel GVCs (Hyunji Kwon and Seri No) -- 6. Formalizing Foreign Manufacturer Status While Deepening Local Embeddedness: Korean Manufacturers in Myanmar's Export-oriented Apparel Industry (Jinsun Bae).
Keywords: Asia -- Economic conditions; Development economics; Globalization; Asian Economics; Development Economics; Globalization